Anaerobic-aerobic digestion of organic fraction of municipal solid waste (OFMSW) - Le, Thi Hong Tran; Rollon, Analiza P.; Nakasaki, Kiyohiko (Quezon City College of Engineering, University of the Philippines Diliman, 2007)
In view of recovering energy resource and reducing emission of greenhouse gases from the organic fraction of municipal solid waste (OFMSW), an anaerobic-aerobic treatment process was considered. For the anaerobic part, we used a two-phase system composed of hydrolytic-acidogenic reactor and a methanogenic reactor, which was an upflow anaerobic sludge blanket reactor (UASB). To avoid accumulation of volatile fatty acids that can inhibit methane generation and hydrolysis in the first phase, it was sprinked with recycled effluent from the second phase (UASB). Two runs were performed at different loading rates. At 4.59 kg COD/m3/d and 21 d SRT in the phase I reactor and overall loading of 2.87 kg COD/m3/d the methane yield was 0.18 m3/kg VS and methane production rate was 0.38 m3/m3/d. The total chemical oxygen demand (TCOD) of the residual solid was 60% of the feed solids TCOD. Of these residual solids TCOD, 33% was dissolved organic matter and 67% remains to be hydrolyzed. This represents 40% of the TCOD of the feed solids. At higher loading rates, methane yield was higher and the amount of the residual solids was lesser. Aerobic composting is generally considered as a necessary post-treatment for residual solids after anaerobic digestion. This study aimed to determine the effects of temperature on biodegradation, pathogen reduction, microbial population density and composition and succession, using PCR-DGGE method, during thermophilic aerobic composting of residual OFMSW after anaerobic digestion (OFMSW-ADR). The results showed that biodegradation was fastest ar 50-60˚C. The density of microbial population was high at 40-60˚C and lowest at 70˚C. After two days of composting, pathogens are inactivated at 50-70˚C, while they increased and persisted at 40˚C. The DGGE band patterns differed both at the initial and end stages among four runs, indicating a strong effect of temperature on microbial communities. The number of bands of DGGE decreased as the temperature rose from 40 to 60˚C except at 70˚C. The microorganisms found by band sequencing were mainly degraders of complex biopolymers through the action of hydrolytic enzymes, some of which are heat-stable. This study ascertained that temperature strongly influences the rate and extend of biodegradation, pathogen control, and the microbial community. In another part of the study, two residual OFMSW after anaerobic digestion were compared. These residues differed in composition due to the differences in the prior anaerobic treatment. The results showed that the organic matter degradation and the change in microbial populations differed between the two runs. These differences are attributable to the differences in the amount of the organic matter and the composition of the residual OFMSW after anaerobic digestion. The PCR-EDDGE analysis demonstrated a clear succession of microbial communities during composting process. This succession can be attributed to the changing composition of the residue.
Vita.
Thesis (Doctor of Philosophy in Environmental Engineering)--University of the Philippines Diliman
Keywords: Organic wastes -- Recycling; Refuse and refuse disposal; Waste products -- Ho Chi Minh City; Waste products -- Metro Manila